Physiology of Spiked Sandal - Parthasarathi, K. (Indian Forester, 1979)
In Sandal (Santalun album Linn.) affected by spike disease, caused by mycoplasma-like organisms, there is (i) an accumulation of carbobydrates, particuluarly starch, (ii) chlorosis and stunted growth of the leaves, (iii) accumulation of phenolic bodies, and increase of polyphenolase activity and IAA content, and (iv) disturbance in mineral, nitrogen and nucleic acid-metabolism. The work done so far on these and other aspects of the physiology of spiked sandal, has been reviewed in this paper.